Peran Media Sosial Dalam Pembentukan Prioritas Isu Publik - Bambang Aditio; Nora Eka Putri; Lince Magriasti (PT. Hasba Edukasi Mandiri, 2026)
Southeast Asia is one of the fastest-growing social media regions in the world, where digital platforms increasingly shape the formation and prioritization of public issues. This study aims to analyze the role of social media in promoting issues to the public and policy agendas, the factors influencing its effectiveness, and the structural limitations that constrain this process. The study applies Agenda Setting Theory and Framing Theory through a Systematic Literature Review (SLR) following the PRISMA 2020 guidelines. Literature was collected from Scopus, Web of Science, SAGE Journals, Taylor & Francis Online, and Frontiers, focusing on open-access articles published between 2018 and 2026 that examined Indonesia and other Southeast Asian countries. A total of 10 articles met the inclusion criteria. The findings identify three major themes: issue mobilization and digital civic participation, issue framing and its influence on policy dynamics, and structural weaknesses including algorithmic bias, misinformation, and digital repression. Social media can serve as an effective agenda-setting catalyst; however, its influence remains highly dependent on the interaction of technological, political, and civic capacity factors.